Kelekatan Kelembagaan: Industri Distro Fesyen di Bandung - Achwan, Rochman (UI Scholars Hub, 2013)
This paper tries to enrich three perspectives for the study of creative industry, cultural entrepreneurship, social contract, and contextual knowledge, by employing an institutional approach and argues that institutional embbededness plays a vital role in promoting creative fashion distro (distribution store) in Bandung that historically well-known city of fashion. Qualitative method has been used to collect data from various informants. This study reveals that disembeddedness between state and creative fashion business and within society of fashion become a mayor feature of the business. As a consequence, creativity of fashion entrepreneurs unable to prosper and internal business organisation is difficult to mature. Recent development, however, indicates that big economic actors and local state begin to co-operate with industry of fashion distro. This development suggests that problems of disembeddedness can be transformed into embeding business actors-state as well as actors within the business. The future of creative fashion distro in Bandung will depend on the struggle of forces of embedding againt disembedding state, the economic, and the association tha support it.